Drug susceptibility of M. tuberculosis in tuberculosis patients from various population groups in Khanty-Mansiyskiy Autonomous Region - Yu. V. Reshetnikova; S. N. Аndreevskaya; E. E. Larionova (New Terra Publishing House, 2015)
The study included 287 cultures of tuberculous mycobacteria received from specimens of patients from Khanty-Mansiysky TB Dispensary in 2011-2012. Patients from Khanty-Mansiysky TB Dispensary have a fairly high rate (24.0%) of co-infection of TB and HIV, especially among urban population (26.8%) compared to rural (13.6%) citizens. When analyzing the drug susceptibility of tuberculous mycobacteria isolated from pulmonary tuberculosis patients it has been found out that multiple drug resistant strains prevailed in the regions (56.8% of all drug resistant strains), and among them in more than a half of cases the strains were resistant not only to HR but to 3-4 additional TB drugs (29.3% of the total number of tested strains), which significantly increases the risk of treatment failure.